1998
DOI: 10.1007/s002469900290
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dexamethasone Therapy on the Neonatal Ductus Arteriosus

Abstract: Patent ductus arteriosus (PDA) is believed to be a contributing factor in the etiopathogenesis of bronchopulmonary dysplasia (BPD). We studied the effects of early dexamethasone therapy on persistent ductal patency and the role of PDA in the etiopathogenesis of BPD during the course of a randomized double-blind trial of dexamethasone to prevent BPD. Infants, who weighed between 700 and 999 g, had severe RDS, and had been given surfactant, were randomized to receive a 12-day course of dexamethasone (n = 13) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Experimentally induced adrenal insufficiency results in greatly amplified inflammation in animal models, with parallels in human disease. 39 -41 Although we postulated that correction of such a deficiency would decrease inflammatory lung injury, the beneficial effects of hydrocortisone seen in this trial may well have resulted from glucocorticoid effects on other organ systems, such as cardiovascular, [42][43][44] intestinal, 33 or renal. 45,46 Many clinical trials of dexamethasone to treat or prevent CLD in premature infants have now been reported, commonly employing a dose of dexamethasone (.5 mg/kg/day) equivalent to 10 to 15 times the dose of hydrocortisone used in this study.…”
Section: Discussionmentioning
confidence: 98%
“…Experimentally induced adrenal insufficiency results in greatly amplified inflammation in animal models, with parallels in human disease. 39 -41 Although we postulated that correction of such a deficiency would decrease inflammatory lung injury, the beneficial effects of hydrocortisone seen in this trial may well have resulted from glucocorticoid effects on other organ systems, such as cardiovascular, [42][43][44] intestinal, 33 or renal. 45,46 Many clinical trials of dexamethasone to treat or prevent CLD in premature infants have now been reported, commonly employing a dose of dexamethasone (.5 mg/kg/day) equivalent to 10 to 15 times the dose of hydrocortisone used in this study.…”
Section: Discussionmentioning
confidence: 98%
“…The causes may range from respiratory distress brought on by diminished lung function to apneic episodes of known or unknown etiology (24,26,31,32). Increased adrenal glucocorticoid production in response to hypoxemia serves a number of adaptive roles, such as augmenting vasoconstrictor responses to circulating catecholamines and promoting lung maturation (11,33). A maximal adrenal response to hypoxemia is often lacking in these patients, necessitating frequent administration of steroids such as dexamethasone and hydrocortisone (66 -68).…”
Section: Discussionmentioning
confidence: 99%
“…A coordinated hypothalamic-pituitary-adrenal (HPA) axis response may confer a variety of protective mechanisms aimed at coping with brief periods of severe hypoxia. For example, hypoxia-induced increases in plasma glucocorticoids may facilitate the closing of the ductus arteriosus, improve vasoconstrictor responses to circulating catecholamines, and promote maturation of the immature lung (11,33,67). Although acute hypoxia-induced increases in plasma corticosterone have been reported in neonatal rats (62,64), a complete understanding of the development, timing, and mechanisms of the HPA axis response to this stimulus has not been elucidated.…”
mentioning
confidence: 96%
“…It is known that the neonatal response to acute hypoxia involves the hypothalamic-pituitary-adrenal (HPA) axis, resulting in an increase in plasma glucocorticoids that promotes lung maturation and improves the vasoconstrictor response to circulating catecholamines (Morales et al 1998;Watterberg et al 1999;Deruelle et al 2003). The rat adrenal zona fasciculata/reticularis produces the glucocorticoid corticosterone through a well-documented ACTH-dependent cAMP-stimulated pathway (Gallo-Payet and Payet 2003).…”
Section: Introductionmentioning
confidence: 99%